The aspect of brands and marketing development in pharmaceutical industry - Veselin Dickov (Acta medica Lituanica, 2012)
The product is something made in a factory; a brand is something that is bought by the customer. A product can be copied by a competitor; a brand is unique. A product can be quickly outdated; a successful brand is timeless. Developing a successful brand yields numerous consumer benefits and also leads to easier accomplishment of market goals: reduced marketing costs due to high levels of brand recognition and express brand loyalty. The basic function of any trademark or brand is to make the product unique, different from others. A brand is a name, term, sign, symbol, or design, or a combination of them, intended to identify the goods or services of one seller or a group of sellers and to differentiate them from those of competitors.